SPIRITUAL AND CULTURAL HERITAGE OF THE UZBEK PEOPLE - Akhmedova Gulchekhra Uskinovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The musical art of the Uzbek people, which occupies an important place in the spiritual culture, dates back to long historical times. Archaeological research conducted in our republic proved that our distant ancestors had a high level of musical art.